Chronic Lactate Exposure Decreases Mitochondrial Function by Inhibition of Fatty Acid Uptake and Cardiolipin Alterations in Neonatal Rat Cardiomyocytes - San-Millan, Iñigo; Sparagna, Genevieve C.; Chapman, Hailey L.; Warkins, Valerie L.; Chatfield, Kathryn C.; Shuff, Sydney R.; Martinez, Janel L.; Brooks, George A. (Frontiers in Nutrition, 2022)
Introduction: Lactate is an important signaling molecule with autocrine, paracrine and endocrine properties involved in multiple biological processes including regulation of gene expression and metabolism. Levels of lactate are increased chronically in diseases associated with cardiometabolic disease such as heart failure, type 2 diabetes, and cancer. Using neonatal ventricular myocytes, we tested the hypothesis that chronic lactate exposure could decrease the activity of cardiac mitochondria that could lead to metabolic inflexibility in the heart and other tissues. Methods: Neonatal rat ventricular myocytes (NRVMs) were treated for 48 hours with 5, 10, or 20 mM lactate and CPT I and II activities were tested using radiolabelled assays. The molecular species profile of the major mitochondrial phospholipid, cardiolipin, was determined using electrospray ionization mass spectrometry along with reactive oxygen species (ROS) levels measured by Amplex Red and mitochondrial oxygen consumption using the Seahorse analyzer. Results: CPT I activity trended downward (p=0.07) and CPT II activity significantly decreased with lactate exposure (p<0.001). Cardiolipin molecular species containing four 18 carbon chains (72 carbons total) increased with lactate exposure, but species of other sizes decreased significantly. Furthermore, ROS production was strongly enhanced with lactate (p<0.001) and mitochondrial ATP production and maximal respiration were both significantly down regulated with lactate exposure (p<0.05 and p<0.01 respectively). Conclusions: Chronic lactate exposure in cardiomyocytes leads to a decrease in fatty acid transport, alterations of cardiolipin remodeling, increases in ROS production and decreases in mitochondrial oxygen consumption that could have implications for both metabolic health and flexibility. The possibility that both intra-, or extracellular lactate levels play roles in cardiometabolic disease, heart failure, and other forms of metabolic inflexibility needs to be assessed in vivo.